Corrigendum to “Assessing the potential for sea-based macroalgae cultivation and its application for nutrient removal in the Baltic Sea” [Sci. Total Environ. 839 (2022) 156230] - J. Kotta; U. Raudsepp; R. Szava-Kovats; R. Aps; A. Armoskaite; I. Barda; P. Bergström; M. Futter; F. Gröndahl; M. Hargrave; M. Jakubowska; H. Jänes; et al. (Science of The Total Environment, 2023)

Publisher Correction: Leveraging research infrastructure co-location to evaluate constraints on terrestrial carbon cycling in northern European forests - Martyn N. Futter; Thomas Dirnböck; Martin Forsius; Jaana K. Bäck; Nathalie Cools; Eugenio Diaz-Pines; Jan Dick; Veronika Gaube; Lauren M. Gillespie; Lars Högbom; Hjalmar Laudon; Michael Mirtl; et al. (Ambio, 2023)

Leveraging research infrastructure co-location to evaluate constraints on terrestrial carbon cycling in northern European forests - Martyn N. Futter; Thomas Dirnböck; Martin Forsius; Jaana K. Bäck; Nathalie Cools; Eugenio Diaz-Pines; Jan Dick; Veronika Gaube; Lauren M. Gillespie; Lars Högbom; Hjalmar Laudon; Michael Mirtl; et al. (Ambio, 2023)
Integrated long-term, in-situ observations are needed to document ongoing environmental change, to “ground-truth” remote sensing and model outputs and to predict future Earth system behaviour. The scientific and societal value of in-situ observations increases with site representativeness, temporal duration, number of parameters measured and comparability within and across sites. Research Infrastructures (RIs) can support harmonised, cross-site data collection, curation and publication. Integrating RI networks through site co-location and standardised observation methods can help answers three questions about the terrestrial carbon sink: (i) What are present and future carbon sequestration rates in northern European forests? (ii) How are these rates controlled? (iii) Why do the observed patterns exist? Here, we present a conceptual model for RI co-location and highlight potential insights into the terrestrial carbon sink achievable when long-term in-situ Earth observation sites participate in multiple RI networks (e.g., ICOS and eLTER). Finally, we offer recommendations to promote RI co-location.

Small artificial waterbodies are widespread and persistent emitters of methane and carbon dioxide - M. Peacock; J. Audet; D. Bastviken; S. Cook; C. D. Evans; A. Grinham; M. A. Holgerson; L. Högbom; A. E. Pickard; P. Zieliński; M. N. Futter (Global Change Biology, 2021)
Inland waters play an active role in the global carbon cycle and emit large volumes of the greenhouse gases (GHGs), methane (CH 4 ) and carbon dioxide (CO 2 ). A considerable body of research has improved emissions estimates from lakes, reservoirs and rivers but recent attention has been drawn to the importance of small, artificial waterbodies as poorly quantified but potentially important emission hotspots. Of particular interest are emissions from drainage ditches and constructed ponds. These waterbody types are prevalent in many landscapes and their cumulative surface areas can be substantial. Furthermore, GHG emissions from constructed waterbodies are anthropogenic in origin and form part of national emissions reporting, whereas emissions from natural waterbodies do not (according to Intergovernmental Panel on Climate Change guidelines). Here, we present GHG data from two complementary studies covering a range of land uses. In the first, we measured emissions from nine ponds and seven ditches over a full year. Annual emissions varied considerably: 0.1–44.3 g CH 4 m −2 year −1 and −36–4421 g CO 2 m −2 year −1 . In the second, we measured GHG concentrations in 96 ponds and 64 ditches across seven countries, covering subtropical, temperate and sub‐arctic biomes. When CH 4 emissions were converted to CO 2 equivalents, 93% of waterbodies were GHG sources. In both studies, GHGs were positively related to nutrient status (C, N, P), and pond GHG concentrations were highest in smallest waterbodies. Ditch and pond emissions were larger per unit area when compared to equivalent natural systems (streams, natural ponds). We show that GHG emissions from natural systems should not be used as proxies for those from artificial waterbodies, and that artificial waterbodies have the potential to make a substantial but largely unquantified contribution to emissions from the Agriculture, Forestry and Other Land Use sector, and the global carbon cycle.

Towards an Improved Conceptualization of Riparian Zones in Boreal Forest Headwaters - José L. J. Ledesma; Martyn N. Futter; M. Blackburn; Fredrik Lidman; Thomas Grabs; Ryan A. Sponseller; Hjalmar Laudon; Kevin H. Bishop; Stephan J. Köhler (Ecosystems, 2018)

Soil temperature responses to climate change along a gradient of upland–riparian transect in boreal forest - S . K. Oni; F. Mieres; M. N. Futter; H. Laudon (Climatic Change, 2017)

Water renewal along the aquatic continuum offsets cumulative retention by lakes: implications for the character of organic carbon in boreal lakes - R. A. Müller; M. N. Futter; S. Sobek; J. Nisell; K. Bishop; G. A. Weyhenmeyer (Aquatic Sciences, 2013)

Simulating Dissolved Organic Carbon Dynamics at the Swedish Integrated Monitoring Sites with the Integrated Catchments Model for Carbon, INCA-C - M. N. Futter; S. Löfgren; S. J. Köhler; L. Lundin; F. Moldan; L. Bringmark (Ambio, 2011)

Assessment of Uncertainty in Long-Term Mass Balances for Acidification Assessments: A MAGIC Model Exercise - S. J. Köhler; T. Zetterberg; M. N. Futter; J. Fölster; S. Löfgren (Ambio, 2011)

Spatial analysis of ice phenology trends across the Laurentian Great Lakes region during a recent warming period - Olaf P. Jensen; Barbara J. Benson; John J. Magnuson; Virginia M. Card; Martyn N. Futter; Patricia A. Soranno; Kenton M. Stewart (Limnology and Oceanography, 2007)
We examined spatial patterns of trends in ice phenology and duration for 65 waterbodies across the Great Lakes region (Minnesota, Wisconsin, Michigan, Ontario, and New York) during a recent period of rapid climate warming (1975‐2004). Average rates of change in freeze (3.3 d decade −1 ) and breakup (22.1 d decade −1 ) dates were 5.8 and 3.3 times more rapid, respectively, than historical rates (1846‐1995) for Northern Hemisphere waterbodies. Average ice duration decreased by 5.3 d decade −1 . Over the same time period, average fall through spring temperatures in this region increased by 0.7°C decade −1 , while the average number of days with snow decreased by 5.0 d decade21, and the average snow depth on those days decreased by 1.7 cm decade −1 . Breakup date and ice duration trends varied over the study area, with faster changes occurring in the southwest. Trends for each site were compared to static waterbody characteristics and meteorological variables and their trends. The trend toward later freeze date was stronger in large, low‐elevation waterbodies; however, freeze date trends had no geographic patterns or relationships to meteorological variables. Variability in the strength of trends toward earlier breakup was partially explained by spatial differences in the rate of change in the number of days with snow cover, mean snow depth, air temperature (warmer locations showed stronger trends), and rate of change in air temperature. Differences in ice duration trends were explained best by a combination of elevation and the local rate of change in either temperature or the number of days with snow cover.